PADLET FOR ENGLISH SPEAKING ACTIVITY: A CASE STUDY OF PROS AND CONS ON ICT - Trisnendri Syahrizal; Silpia Rahayu (University of Kuningan, 2020)
As Millennial generation, students nowadays have limitless concept of time and space, they broke logical and physical barriers during the process of communication including in the process of learning. Blanded learning and hybrid learning are one of the latest phenomenon in Education. In shortest perception students will encoder positive effect toward the uses of technology in school but in fact some of them also encounter obstacle and problems. This research aims to project the students’ pros and cons on the use of one of ICT called PADLET during the process of speaking activity. This research uses 35 students of one private university in Cimahi, Indonesia. Qualitative method used to provide detail finding associate with supportive theories. Observation that was taken from both online processes during submitting and commenting the speaking video and offline situation were used and then strengthen by the use of open questions interview. From the data, it showed that students pros on the idea of; (1) collaboration, (2) Flexibility. (3) Autonomous Learning. While on cons students mark on; (1) technicality issue, (2) Psychological elements. Keywords: ICT; PADLET; Pro; Cons; Speaking.